Microplastic pollution in surface water from east coastal areas of Guangdong, South China and preliminary study on microplastics biomonitoring using two marine fish. (October 2020) - Zhang, Chaonan; Wang, Shaodan; Sun, Di; Pan, Zhenkun; Zhou, Aiguo; Xie, Shaolin; Wang, Jun; Zou, Jixing
Abstract: Microplastic pollution, one of the major global challenges, is a severe threaten to aquatic organisms. The purpose of this study was to investigate the abundance, distribution and characteristics of microplastics in coastal surface waters from eastern Guangdong, south China. We chose pelagic Konosirus punctatus and demersal Mugil cephalus from different sampling sites as candidate monitoring species for the ingestion of marine microplastics, and talked about the relationship between water samples and fish samples. We tried to find out the regulation about microplastics characteristics in fish samples and fish own traits. The mean abundance of microplastics in surface water was 8895 items/m 3, small white fragments were dominating character. We need to increase the amount of fish data to further explore. This study would not only provide a detailed reference for a better understanding of microplastic pollution in Guangdong coastal areas, but also shed an insight in prospect of using fish as biomonitoring of microplastic wastes. Graphical abstract: Image 1 Highlights: Small white fragments were dominating character of microplastics from east coastal areas of Guangdong, south China. There was no significant relationship between the number of fish ingestion microplastics and fish length, weight or GITs weight. There was no significant relationship between average microplastic abundance of water samples and two fish samples.